Ethics and Methods for Collecting Sensitive Data - Bachera Aktar; Rushdia Ahmed; Raafat Hassan; Nadia Farnaz; Pushpita Ray; Abdul Awal; Sharid Bin Shafique; Md Tanvir Hasan; Zahidul Quayyum; Mohira Babaeva Jafarovna; Loulou Hassan Kobeissi; Khalid El Tahir; et al. (The International journal of information, diversity, & inclusion, 2020)
During humanitarian emergencies, such as the forced displacement of the Rohingya diaspora, women and adolescent girls become highly vulnerable to sexual and reproductive health (SRH) issues and abuse. Although sensitive in nature, community-driven information is essential for designing and delivering effective community-centric SRH services. This article provides an overview of the theoretical framework and methodologies used to investigate SRH needs, barriers, and challenges in service-delivery and utilization in the Rohingya refugee camps in Cox’s Bazar, Bangladesh. It also offers insights on important methodological and ethical factors to consider while conducting research in a similar context. A concurrent mixed-method study was undertaken in ten randomly selected Rohingya refugee camps between July and November 2018. The design consisted of a cross-sectional household survey of 403 Rohingya adolescent girls and women, along with an assessment of 29 healthcare facilities. The team also completed in-depth interviews with nine adolescent girls, 10 women, nine formal and nine informal healthcare providers, key informant interviews with seven key stakeholders and seven influential community members. Lastly, three focus group discussions were undertaken with a group of 18 Rohingya men. Our theoretical framework drew from the socio-ecological models developed by Karl Blanchet and colleagues (2017) insofar as they considered a multiplicity of related contextual and cross-cutting factors. Building good rapport with community gatekeepers was key in accessing and sustaining the relationship with the various respondents. The data collected through such context-specific research approaches is critical in designing community-centric service-delivery mechanisms, and culturally and gender-sensitive SRH interventions in humanitarian crises.